How ICT and teacher attitudes shape math achievement: A structural equation model from Ghana’s secondary education - Arhin, Jacob; Arthur, Yarhands Dissou; Gordon, Joseph Frank (American Journal of STEM Education, 2025)
In this study, we examine the impact of ICT integration on high school students’ mathematics achievement, with a focus on the moderating role of teachers’ attitudes toward technology. Data were gathered from 500 mathematics teachers using a multi-stage sampling method and analyzed using Structural Equation Modeling (SEM). Findings reveal a positive relationship between ICT use and mathematics performance. Notably, teachers’ positive attitudes toward ICT significantly strengthen this effect, highlighting the importance of teacher disposition in effective technology integration. The study highlights the importance of professional development that enhances both technical ICT competencies and positive attitudes. These results provide key insights for educational policy and instructional strategies aimed at improving learning outcomes through technology